210-Day Kinetics of Total, IgG, and Neutralizing Spike Antibodies across a Course of 3 Doses of BNT162b2 mRNA Vaccine - Chin Shern Lau; May Lin Helen Oh; Soon Kieng Phua; Ya-Li Liang; Tar Choon Aw (Vaccines, 2022)
Introduction: We tested the total spike antibody (S-Ab), IgG/IgM S-Ab, and neutralizing antibody (N-Ab) responses of COVID-19-naïve subjects from before their first BNT162b2 vaccination up to 210 days after boosting. Methods: We studied 136 COVID-19-naïve subjects who received three doses of the Pfizer mRNA vaccine (39 males, 97 females, mean age 43.8 ± 13.5 years) from January 2021 to May 2022. Serum was assessed for total S-Ab (Roche), IgG/M (Abbott), and N-Ab (Snibe). Results: Peak antibody levels were measured 20-30 days after each dose, with booster dosing eliciting significantly higher peak antibodies than the second dose: total S-Ab 2219 vs. 19,551 BAU/mL (difference 16,667 BAU/mL, p < 0.0001); IgG 2270 vs. 2932 BAU/mL (difference 660 BAU/mL, p = 0.04); and N-Ab 3.52 vs. 26.4 µg/mL (difference 21.4 µg/mL, p < 0.0001). Only IgM showed a lower peak post-booster antibody titer (COI 2.11 vs. 0.23, difference 1.63, 95% CI 1.05 to 2.38, p < 0.0001). By 180–210 days after the second or third vaccination, total S-Ab/IgG/N-Ab had decreased by 68.7/93.8/73.6% vs. 82.8/86.3/79.5%. The half-lives of IgG and N-Ab antibodies were longer after the third vaccination (IgG: 65 vs. 34 days, N-Ab: 99 vs. 78 days). Conclusion: Total S-Ab/IgG/N-Ab showed a greater increase post-booster, with IgG/N-Ab having a longer half-life.